Numerical investigation of lamella heat exchanger for engine intake charge air cooling utilizing refrigerant as coolant medium - Ikhtiar, Usman; Hairuddin, Abdul Aziz; Asarry, Azizan; Md Rezali, Khairil Anas; Muhammad Ali, Hafiz (Elsevier, 2022)
Intercooler heat exchangers (IHE) are used to improve engine charge air temperature, which enhances engine efficiency and reduces emissions. The current study introduces a novel intercooler heat exchanger designed to improve combustion and engine performance by providing cold intake air. Lamella heat exchanger is proposed, based on space availability in existing engines, operated as an evaporator utilizing a refrigeration unit, the same used for vehicle compartment cooling. A numerical investigation is carried out for a 1.496 L naturally aspirated engine at rpm 4000, 5000, and 6000. The intake air temperature is taken as 45 °C to examine the proposed four models: model A, model B, model C & model D bearing aspect ratios of 21.6 mm, 27 mm, 36 mm & 43.2 mm, respectively. The study aims to obtain high heat transfer with minimal pressure loss. For that, the evaluation criteria for all models are heat transfer, temperature drop, number of transfer units, logarithmic mean temperature difference, and pressure drop. As a result, all models under consideration are ranked from high to low; model D, model C, model B, and model A. The maximum heat transfer of 1.55 KW and the maximum temperature drop of 24.06 °C are observed for model D at rpm of 6000 and 4000, respectively. Likewise, the maximum pressure drop is recorded for model D at all rpm ranges; still, the pressure drop for model D is less than 28 % of the reference model used in this study at 6000 rpm. The simulated results indicate that all evaluation parameters except LMTD are directly proportional to the aspect ratio of the lamella. Due to their compactness, the proposed heat exchanger designs offer more surface area per unit volume, resulting in higher thermal capacity than the other conventional intercooler heat exchangers.